ANALISIS PERBANDINGAN PERILAKU KONSUMEN DI PASAR TRADISIONAL DAN E-COMMERCE - Putri, Marizka Shabira; Rabbani, Ridho Bari; Salma, Ilma Fatikah; Hidayah, Nurul (ANALISIS, 2024)
Technological developments characterized by easy access to the internet among the public have changed the pattern of life from traditional to a more modern and instantaneous one. Likewise, the economic sector has experienced a significant impact due to technological advances, one of which is the increase in the form of digital or electronic commerce. The research objectives aim to determine the condition of the market after e-commerce, then the effect of product quality, service quality, price perceptions, trust, and location on consumer purchasing decisions, knowing the relationship between purchasing decisions and market form selection, and knowing market form opportunities that provide more benefits to business actors. The population in this study is all consumers domiciled in Depok City who transact at Tugu Pal Market or e-commerce, and determining the number of samples for interviews with fashion traders using the Slovin formula at a precision level of 10% obtained as many as 43 samples. The analysis method used, namely the multiple linear regression analysis test, t test, and Mann-Whitney U-test, obtained information that in traditional markets product quality and trust have a significant effect, while in e-commerce the variables of service quality, price perception, and trust have a significant effect on purchasing decisions. In addition, there are changes in conditions in traditional markets after e-commerce.